(untitled) (Confluenţe Bibliologice, 2012)
The study presents the results of a survey conducted by the University Library on the basis of scientiﬁc research users (teachers) on the science communication in the academic environment; the digital culture; some of the obstacles that appear in the publication of articles in foreign journals. The results of the questionnaire shows a clear picture of teachers’views on the communication in science (documentation, their own research) and communication about science (communication of results); improving the quality of information services rendered by the library: modernization, access to foreign literature; information skills training courses, access to specialized international magazines.